2013
DOI: 10.5114/pjp.2013.38134
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of ERG-positive prostate carcinoma in Poland

Abstract: Prostatic carcinoma (PC) is one of the most frequent cancers in men. Molecular pathogenesis of PC remains poorly understood. Translocations involving ERG were found to be the single most frequent genetic event. A strong correlation exists between this translocation and ERG positivity on immunohistochemistry. The rate of ERG positivity and its relationship with other clinicopathological parameters differ between populations and between studies; in particular, there are few data on ERG-positive PC in Eastern Eur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 25 publications
3
7
0
Order By: Relevance
“…Its molecular pathogenesis is complex, yet a significant proportion of cases bear recurrent translocation involving ETS family genes; this results in increased expression of ETS transcription factors, most frequently ERG, which may be easily detected by immunohistochemistry [3,4]. In one of our previous studies, the frequency of ERG positivity in PC was 46%, which is similar to other European populations [5]. We found that ERG-positive PC have a higher number of microvessels [6].…”
Section: Introductionsupporting
confidence: 63%
See 1 more Smart Citation
“…Its molecular pathogenesis is complex, yet a significant proportion of cases bear recurrent translocation involving ETS family genes; this results in increased expression of ETS transcription factors, most frequently ERG, which may be easily detected by immunohistochemistry [3,4]. In one of our previous studies, the frequency of ERG positivity in PC was 46%, which is similar to other European populations [5]. We found that ERG-positive PC have a higher number of microvessels [6].…”
Section: Introductionsupporting
confidence: 63%
“…The slides were counterstained with Mayer's hematoxylin (Thermo Fisher Scientific, Waltham, USA) and coverslipped. The results of the ERG staining were scored as positive when unequivocal nuclear staining was present; very faint nuclear as well as any cytoplasmic reaction was ignored, as previously reported [5]. The slides for tryptase ( Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The LabVision detection system (Thermo Scientific, USA) was used for each staining. The results of the ERG staining were scored as positive when unequivocal nuclear staining was present; very faint nuclear as well as any cytoplasmic reaction was ignored, as previously reported [11]. The FOXP3 expressing cells were counted in each tissue microarray core and the results were expressed as the number of cells per mm 2 .…”
Section: Methodsmentioning
confidence: 99%
“…There are over 540 000 new cases diagnosed each year worldwide [5]. It occupies second place in mortality in Poland and first place in the USA [6,7].…”
Section: Introductionmentioning
confidence: 99%